Cranial nerve injury during transcarotid transcatheter aortic valve replacement. (15th April 2022) - Panagides, Vassili; Kalavrouziotis, Dimitri; Dumont, Eric; Delarochellière, Robert; Paradis, Jean-Michel; Mesnier, Jules; Mohammadi, Siamak; Rodés-Cabau, Josep
Abstract: Background: No data exist about cranial nerve injury (CNI) as a potential complication of transcarotid (TC) transcatheter valve replacement (TAVR). Methods: This monocentric study included 318 consecutive patients undergoing TC-TAVR from May 2015 to August 2021. Results: CNI occurred in 7 (2.2%) TAVR-TC patients. Five out of the 7 patients (71.4%) had an injury of the laryngeal branch of the vagus nerve, and 2 patients (28.6%) had an injury of the facial nerve. The majority of patients were male (85.7%), with high body mass index (35.6 (IQR: 30.1–37.3) kg/m2). The induced disabilities were clinically important especially for patients with dysphonia. Conclusions: CNI is a potential complication of TC-TAVR likely avoidable by a meticulous surgical technique. Structural heart teams must be aware of this serious setback. Highlights: Severe dysphonia or peripheral facial paralysis after TC-TAVR can be related to CNI. These injuries are likely avoidable by a meticulous surgical dissection. TAVR team must be aware of this setback to prevent it and inform the patient.